Peran PKS Dalam Pendidikan Politik Pada Masa Pandemi Covid 19 Di Kalidoni Palembang - Yunizar, Muhammad; Rochmiatun, Endang (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
Abstract The current condition of the Covid-19 pandemic that Indonesia is currently experiencing requires people to avoid gatherings and maintain social distancing. With this condition, how is the role of political parties in political education during the Covid-19 pandemic (Study on the Prosperous Justice Party at the DPC PKS, Kalidoni District, Palembang City. To analyze the research results, the writer uses role theory, political party theory and political education theory. This study uses a qualitative method with a descriptive approach. By using the primary data sources, namely observations and interviews, while the secondary data is obtained from the results of documentation, books, journals, and other reports from the results of related research. The results of this study found that the forms of political education during the Covid-19 pandemic at the Prosperous Justice Party at the DPC PKS Kalidoni District, Palembang City were divided into three target audiences, namely for individual parties through the Political Recruitment and TOP (Party Orientation Training) program with regular carried out during the pandemic to facilitate party individuals with legal and political insight, then programs aimed at party administrators including the khalaqah program and political education through webinars, finally political education aimed at the community through the Mothers Motivator and Pioneer of Kindness Political Education program which is still being carried out at the sub-district level during the pandemic by implementing physical distancing and BPJE (Economic Network Empowerment Sector) which was conducted in a webinar and was specifically aimed at MSME actors. The supporting factors were technology facilities and quality The human resources owned by PKS and the inhibiting factor is the lack of community involvement where the community still does not have adequate technology and inadequate infrastructure The role and strategy of the Prosperous Justice Party (PKS) in Conducting Political Education During the Covid-19 Pandemic by utilizing technology in the current era of the covid-19 pandemic Keyword : Covid-19, Political Parties, Political Education